A Comparative Study of Vendor Selection Process in Global Outsourcing Industry with an Elucidated Scientific Approach - et. al., Dr. Abhay Juvekar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
While short listing a vendor, all stakeholders want to ensure that a reliable, dependent, and quality vendor is on-boarded. Any rogue or incompetent vendor selection may hamper the core business of the organization and may result in the downfall of the organization as well as its goodwill, built over years. Stemming from this dilemma, business leaders moved to the business process outsourcing model to mitigate some of the risks in doing everything by them. The outsourcing helps to quickly scale up or scale down and avail expert services at a reasonable price. While mitigating risks, this also allows the parent organization to focus on their core business lines. Increasing reliance on outsourcing of business processes requires a more robust, systematic, and reliable strategy/technique rather than a trial-and-error method based on human-relations and interviews. There exist various methods proposed in past and are also being explored under the garb of Decision Analysis and Resolution or Decision Support Systems. However, research shows considerable use of such systems and methods in the work methodology rather than for Vendor selection. In this paper, we lay focus on an IT outsourcing scenario where a standard decision method can be used while comparing global vendors in this highly dynamic, competent IT Business Scenario.